Nonlinear interaction between ocean tides and the Larsen C Ice Shelf system - Matt King; Makinson, K; Gudmundsson, GH (2011)
We report on three GPS records of flow of the Larsen C Ice Shelf, spanning 2 months to 2 years. Variations in speed are evident at periods from a few hours to âˆ¼182 days, including semi-diurnal, diurnal and âˆ¼14.76 days. At fortnightly periods the ice shelf varies by 10% from its long-term speed but at diurnal timescales it is up to 100%. A nonlinear relationship between ocean tides and velocity is required to explain the observed variations in flow. As an initial examination we model flow as a non-linear function of basal shear stress including tidal perturbations in the ice shelf grounding zone and show that the major features of the observations are reproduced, notably the long-period signal largely absent from the vertical tidal signal. Alternative explanations are discussed. These observations demonstrate that the ice shelf system is highly sensitive to relatively modest changes in forcing at its boundaries. Copyright 2011 by the American Geophysical Union.